What comes before phonics? - Neaum, Sally (Sage, 2017)
"This book looks in detail at the knowledge, understanding, skills and attitudes that children need to enable them to come to phonics teaching ready to learn and with a good chance of success. It explores a range of aspects of young children's learning that lead into literacy, and includes practical advice on how to translate this into practice"--Back cover.